Structural and functional analysis of Bacillus cereus spore cortex lytic enzymes and YlaJ/YhcN lipoproteins - Mustafa, Amin; Al Riyami, Bahja; Ow-Young-Villarreal, Giannina; Caldbeck, Rebecca; Pin, David Chan Hian; Yarrow, Joshua; Christie, Graham (Microbiology (Society for General Microbiology), 2025)
Resumption of the planktonic phase of the Bacillus cereus cell cycle necessitates degradation of certain morphological structures and physiological features that confer metabolic dormancy and multi-factorial resistance properties to the spore form of the bacterium. Depolymerization of the peptidoglycan cortex, which is crucial to maintenance of spore dormancy, constitutes a major germination event and is conducted by a complement of spore cortex lytic enzymes that are active only during spore germination. This work reports on the structure and function of the major cortex lytic enzymes in B. cereus spores, revealing insight to their location, individual contributions to germination when triggered by different routes and regions of the SleB protein that are important for mediating interactions with its peptidoglycan substrate. The effect of null mutations to lipoproteins of the YlaJ/YhcN family on spore properties is also characterized, revealing parallels with prior observations concerning YlaJ’s influence on SleB activity during germination. Finally, a structural model of a putative SleB-YpeB-YlaJ complex is presented. The model, which was subject to an initial validation by evolutionary covariance analysis and site-directed mutagenesis, reveals how the SleB protein might be held in an inactive state courtesy of its interactions with YpeB and YlaJ during spore dormancy, potentially shedding light on a long-standing puzzle in spore germination.